OPTIMASI PENJADWALAN PRAKTEK DOKTER INSTALASI GAWAT DARURAT (IGD) MENGGUNAKAN METODE PEWARNAAN GRAF DI RUMAH SAKIT UMUM DAERAH PETALA BUMI PROVINSI RIAU - Andriani, Ade Novita; Tonis, Marian; Zaky, Abdul (LPPM Universitas Awal Bros, 2022)
Doctor scheduling at the Emergency Installation (IGD) of the Petala Bumi Regional General Hospital, Riau Province, is carried out in three shifts, namely the morning shift, afternoon shift and night shift. Each shift is scheduled for three to four doctors, with a total of 14 doctors. There are quite a lot of doctors in the emergency room at the Petala Bumi Hospital, Riau Province, so it will require at least a fee. This can be optimized by doing a simpler schedule so that the costs incurred can be reduced. The results of the observations concluded that each shift only needed two doctors to practice in the emergency room at the Petala Bumi Hospital. Optimal Scheduling will greatly reduce or minimize the number of Doctor HR in Petala Bumi Hospital, Riau Province. This research is a type of quantitative researcher with an experimental research design of Development Research (development). The graph coloring is done for four days because, in the matrix the graph coloring pattern repeats itself after the fourth day. Scheduling for four days, graph coloring has 10 colors or chromatic numbers assuming three shifts and two doctors in one shift, so optimizing the preparation of the doctor's schedule at the emergency room of the Petala Bumi Hospital can be done with a minimum of 10 doctors. The impact obtained from the results of optimizing the number of existing doctors is the cost or cost at the hospital, one of which is the doctor's salary can be reduced. The workload carried out also remains in accordance with the number of doctors owned and the preparation of the doctor's schedule can be more optimal.